2009
DOI: 10.1175/2009jtecha1250.1
|View full text |Cite
|
Sign up to set email alerts
|

Polar Stratospheric Cloud Observations in the 2006/07 Arctic Winter by Using an Improved Micropulse Lidar

Abstract: The potential of a new improved version of micropulse lidar (MPL-4) on polar stratospheric cloud (PSC) detection is evaluated in the Arctic over Ny-Å lesund (798N, 128E), Norway. The campaign took place from January to February 2007 in the frame of the International Polar Year (IPY) activities. Collocated Alfred Wegener Institute (AWI) Koldewey Aerosol Raman Lidar (KARL) devoted to long-term Arctic PSC monitoring is used for validation purposes. PSC detection is based on lidar retrievals of both backscattering… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 34 publications
1
1
0
Order By: Relevance
“…A good performance of the MPL-4 system for PSC detection was previously achieved in the Arctic (Córdoba-Jabonero et al, 2009), where depolarization data confirmed that all the PSC cases detected during the 2006-2007 winter were related only to PSC-I events, and no PSC-II occurrences with larger δ V values were found. In particular, the MPL-4 performance for discriminating Type I (Ia and Ib) and Type II PSCs in relation with the δ V parameter is still to be evaluated.…”
Section: Introductionsupporting
confidence: 69%
“…A good performance of the MPL-4 system for PSC detection was previously achieved in the Arctic (Córdoba-Jabonero et al, 2009), where depolarization data confirmed that all the PSC cases detected during the 2006-2007 winter were related only to PSC-I events, and no PSC-II occurrences with larger δ V values were found. In particular, the MPL-4 performance for discriminating Type I (Ia and Ib) and Type II PSCs in relation with the δ V parameter is still to be evaluated.…”
Section: Introductionsupporting
confidence: 69%
“…MPL technology was also improved to increase the system's reliability . Recently, MPLs have been used to study optical properties of clouds Shiobara, Yabuki, and Kobayashi 2003;Campbell and Sassen 2008;Cordoba-Jabonero et al 2009) and aerosols Anderson et al 2000;Welton et al 2002;Voss et al 2001). The primary commercial manufacturers of MPLs are Sigma Space Corporation 1 and Science and Engineering Services, Inc. Table 2-9) to allow the MPL to scan vertically and horizontally.…”
Section: Micropulse Light Detection and Ranging Tapered Element Oscimentioning
confidence: 99%